A Modified Techniques of Fractional-Order Cauchy-Reaction Diffusion Equation via Shehu Transform. (26th July 2021) - Areshi, Mounirah; Zidan, A. M.; Shah, Rasool; Nonlaopon, Kamsing
Abstract : In this article, the iterative transformation method and homotopy perturbation transformation method are applied to calculate the solution of time-fractional Cauchy-reaction diffusion equations. In this technique, Shehu transformation is combined of the iteration and the homotopy perturbation techniques. Four examples are examined to show validation and the efficacy of the present methods. The approximate solutions achieved by the suggested methods indicate that the approach is easy to apply to the given problems. Moreover, the solution in series form has the desire rate of convergence and provides closed-form solutions. It is noted that the procedure can be modified in other directions of fractional order problems. These solutions show that the current technique is very straightforward and helpful to perform in applied sciences.